A Theoretical Framework on EBIT- EPS Analysis - Anitha.A; Aartheeswari. E; Rajalakshmi. K; Rajavel. R (International Journal of Psychosocial Rehabilitation, 2020)
In deciding the capital structure of firm the financial managers depends on EBIT – EPS analysis to find which capital structure gives the maximum Earnings per share (EPS) over the expected Earnings before interest and tax. It is used to find the impact of various financial plans with respect to earnings available to equity shareholders. This study aims to focus on how EBIT-EPS analysis works, its merits & demerits.